Agarose-biofunctionalized, dual-electrospun heteronanofiber mats: toward metal-ion chelating battery separator membranes1. Issue 20 (28th May 2015) - Kim, Ju-Myung; Kim, Chanhoon; Yoo, Seungmin; Kim, Jeong-Hoon; Kim, Jung-Hwan; Lim, Jun-Muk; Park, Soojin; Lee, Sang-Young
<x xml:space="preserve">Abstract</x> We demonstrated an agarose-biofunctionalized, dual-electrospun heteronanofiber mat as a new class of chemically active (specifically, metal-ion chelating) separator membranes for high-performance Li-ion batteries.